2017
DOI: 10.1007/s11912-017-0618-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Periocular Cancers: High- and Low-Risk Features Drive Treatment

Abstract: Mohs excision of basal cell carcinoma and squamous cell carcinoma continues to provide the greatest success in complete excision of the cancer, especially in those cases of high-risk disease including medial canthal location and recurrent disease. Sentinel lymph node biopsy has proven useful in the assessment of early regional metastasis in sebaceous cell carcinoma, melanoma, and Merkel cell carcinoma. The pathologic finding of perineural invasion is a high-risk feature in all periocular cancers, and adjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
0
10
0
1
Order By: Relevance
“…Full-thickness eyelid tumor resection with posterior lamellar is the golden standard and superior to non posterior lamellar resection [25,26]. Mohs surgery has been recommended as treatment of sebaceous carcinoma with excellent results with 11% recurrence rate for primary tumours [27][28][29][30][31]. However, Mohs surgery is resourcesand time-demanding and not available everywhere.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Full-thickness eyelid tumor resection with posterior lamellar is the golden standard and superior to non posterior lamellar resection [25,26]. Mohs surgery has been recommended as treatment of sebaceous carcinoma with excellent results with 11% recurrence rate for primary tumours [27][28][29][30][31]. However, Mohs surgery is resourcesand time-demanding and not available everywhere.…”
Section: Treatmentmentioning
confidence: 99%
“…Pfeiffer et al [50] have reported SLNB to identify nodal micrometastasis in 20% of ocular adnexal melanoma cases. However, in tumors, such as sebaceous carcinoma, that spread via the lymphatic system before spreading systematically SLNB is justifiable in tumors with a significant metastatic risk [30].…”
Section: Fig 4 Scanning For Regional Lymph Nodes or Metastatic Diseamentioning
confidence: 99%
See 2 more Smart Citations
“…5 d), welches chirurgisch mittels eines großen Sicherheitsabstands sowie ggf. auch mittels adjuvanter Bestrahlung angegangen werden sollte [14]. Trotzdem ist der Verlauf bei neurotropem Wachstum oft durch Rezidive gekennzeichnet.…”
Section: Plattenepithelkarzinomunclassified